Factors of taking supplements / Nurul Atika Suria Kelana, Suhaizah Abdullah Nur and Azira Abdul Razab - Kelana, Nurul Atika Suria; Abdullah Nur, Suhaizah; Abdul Razab, Azira (Faculty of Communication & Media Studies, 2018)
Supplement aims is to protecting people from any kinds of disease and helps to build up metabolism. As living in a 3rd world countries Malaysian has apply more supplement in the 21st century. This study is about how acceptance citizen towards supplements as there is still citizen with a traditional supplement. This is study involves 450 respondents selected from a variegated race in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scale previously researchers. Result for the survey show the level of confident towards supplement is low (M=2.76) and whereas the level of healthcare is also high (M=2.95).